PEMAHAMAN TEKSTUAL DAN KONTEKSTUAL PAKAR HADIS DAN PAKAR FIKIH SEPUTAR SUNNAH NABI - Mukhtar, Mukhlis (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2011)
This article outlines the problems and contextual expert understanding of textual tradition and fiqh scholars about the Sunnah of the Prophet, (The criticism of the notion of Shaykh Muhammad al-Ghazali). From the results obtained by the understanding that assessment; Sheikh Muhammad Al-Ghazali was a productive scientist and muballiq. He was very critical in exploring the teachings of Islam are not easily influenced by an opinion that has been established and do not be fooled by the saheeh's a tradition, for his understanding judged have a discrepancy with the main source of understanding the Quran. Understand a verse or hadith textual understanding is absolutely necessary it's just not just stop there. Therefore, understanding the contextual needs to be seen to be a verse or hadith is not understood partially. In this case, the need for cooperation between jurists and muhaddis in researching and examining a Nabawiyyah Sunnah, because a series of narrators in the sanad is strong does not guarantee the validity of honor can help her.